Control de inventarios aplicando la NIC 2 de la Empresa Urdatel S. A. del cantón Urdaneta en el periodo 2022 -2023. - Acosta Troya, Jhon Alexande (2024)
This case study was carried out in the company Urdatel S.A. of the Urdaneta canton with the objective of analyzing inventory control applying IAS2 in the period 2022-2023 and its effects on the profitability of the company, through the review of accounting records. The methodology used consisted of a mixed approach, types of descriptive, documentary and field research, as well as inductive and deductive methods, interview techniques and documentary review. The results were: the company does not have adequate accounting control of the inventory in accordance with what is established by IAS 2, the accountant does not have in-depth knowledge about IAS 2, the company does not have established policies to ensure compliance with the regulations. international accounting. The inventory rotation in the 2023 period was slower than the previous year, that is, it took 63 days to rotate each of the stocks it has. The rotation has not affected the financial situation of the organization. In conclusion, the current situation of inventory control in Urdatel is based on the fact that the procedure to record the value of the inventory in the accounting book consists only of the recognition of the acquisition cost of the products and the net realizable value is not determined to avoid the overvaluation of inventory. The financial analysis of inventory rotation allowed us to determine that in 2023 the company took longer to rotate each of the stocks.